(untitled) (Indian Journal of Forensic Medicine & Toxicology, 2020)
Dermatoglyphics is a scientific study which involves the study of fingerprints.lines ,mounts and shapes of hands.This dermatoglyphics origin dates back to ancient India, were this ridge pattern study was known as “Samuda Sashtra.These dermatoglyphic patterns are usually genetically determined.In dentistry, dermatoglyphics have been applied for identifying syndromic cases and also been useful for determining caries susceptibility,identification of cleft lip and cleft palate. Here the variations of dermatoglyphic patterns among smoking and smokeless forms of tobacco in oral potentially malignant disorders and oral carcinoma has been reviewed.